ANALYSIS OF ARGUMENTATION WRITING ABILITY USING THE OBSERVATION MODEL IN HIGH SCHOOL STUDENTS IN THE 10th CLASS OF THE 2nd SEMESTER in the 2018/2019 ACADEMIC YEAR - Anggraeni, Leni; Puspita, Dian (JLCEdu (Journal of Learning and Character Education), 2021)
Many people are fluent in speaking, but they are not able to express ideas in writing. Even if the speech experts are able to write down their ideas well, this usually happens after going through intensive training, both formally and informally. The ability to write is the result of a learning process and perseverance in practicing. The description in writing the argumentation from the students' observations is still not complete. To examine the ability to write arguments based on observations of high school students in the second semester of 10th class at SMA PGRI Talangpadang, the observation method was used, and sample testing with a population of students in the second semester of 10th class at SMA PGRI Talangpadang. Based on the results of the research data analysis that the author has done, the author can conclude that the average ability of students in the second semester of 10th class at SMA PGRI Talangpadang in 2018/2019 in writing arguments based on observations is quite good (65.25%).